Investigating The Fifth Semester Students Ability of Stmik Pelita Nusantara In Toefl - Ersika Puspita Dani (Jurnal Media Informatika, 2021)
The objectives of this descriptive qualitative study were (1) to find out the student’s ability in TOEFL and (2) to identify the TOEFL sub skills which were required in the improvement. Twenty three students of class MI V Reguler and Executive Class in STMIK Pelita Nusantara Lubuk Pakam were conducted as participants. To examine students’ TOEFL scores, a paper-based TOEFL test was used. The test scores were used to find out the students’ ability at the beginning of the study. Then, the results were analyzed to identify the students’ problem in sub-skills of TOEFL. The data were identified and sub-skill was identified based on Phillips (2003). The findings of the study showed that: (1) the fifth semester students’ ability of STMIK Pelita Nusantara in doing TOEFL test is at Poor level with the most dominant score is below 400, consists of 21 students in that level with 91.30%. Then, there were only a few students, 2 persons with the percentage 8.69%. (2) the fifth semester students’ of STMIK Pelita Nusantara Nusantara is considered as the most difficult for them with the avarage of 5.28 is the listening, while reading section is considered as the easiest one for the fifth semester students of STMIK Pelita Nusantara, with the average of 6.94. Based on the findings, it can be concluded that overall all of the students in this study required further training to improve their TOEFL scores; therefore, it recommended the development of module and training plans according to the outcomes of this analysis study.